Critical thinking dispositions as a mediator between teachers' knowledge and 21st century teaching in Selangor, Malaysia - Mohamad, Azlida; Tajularipin; Ahmad Fauzi (Penerbit UTM Press, 2023)
The study was carried out to bridge the research gap on 21st century teaching; the relationship between pedagogy, content, and technology with 21st century teaching; and the development of critical thinking dispositions. Current study aims to determine the mediating effect of critical thinking dispositions for the relationship between teacher’s knowledge (pedagogy, content, and technology) with 21st century teaching among secondary teachers in Selangor, Malaysia. This study employed causal relationship design with proportional stratified random sampling. In data analysis, inferential statistical is applied to determine the mediating effect through Structural Equation Modeling (SEM). The findings show a significant mediating effect of critical thinking dispositions for the relationship between pedagogical knowledge, content knowledge, and technological knowledge with 21st century teaching. As a conclusion, the mediating model suggests pedagogical knowledge, content knowledge, and technological knowledge with critical thinking dispositions as mediator contributing 61 percent of the variance to 21st century teaching. This final model can be considered by teacher as the efforts to enhance 21st century teaching.